Against the grain (A rebours) - Huysmans, J.-K. (Joris-Karl), 1848-1907
"Against the Grain" by J.-K. Huysmans is a novel written in the late 19th century. The story follows the life of Des Esseintes, the last descendant of a once-noble family, as he seeks refuge from a society he finds unbearable. The opening chapters delve into his solitary existence, intricate aesthetics, and profound disdain for the world around him, exploring themes of decadence and ennui. The beginning of "Against the Grain" introduces Des Esseintes, a young man suffering from a multitude of ailments and the weight of his family's decline. Raised in isolation and viewed as an oddity, he reflects on his upbringing, relationships, and eventual disillusionment with societal norms. Des Esseintes struggles with loneliness while yearning for beauty and meaning, leading him to create a unique sanctuary at his new residence in Fontenay, where he meticulously designs his living space to reflect his artistic sensibilities. Through his somber meditation on existence and sensuality, he ultimately seeks to escape human folly and engage with a more refined, contemplative existence. (This is an automatically generated summary.)